Establishment History and Concept of Surrogate Motherhood - Nuralievich, Yuldashev Sherali (International Journal on Orange Technologies, 2023)
The article covers the concept of surrogate motherhood, the history of its emergence, formation and development, as well as the general principles and legal nature of the use of surrogate motherhood, the legislation of some countries of the world, and issues related to the topic of some researches carried out in this direction.